2016
DOI: 10.1128/aem.00520-16
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring of the Aquatic Bacterial Community by Hydric Dynamics Associated with Superstorm Sandy

Abstract: Bacterial community composition and longitudinal fluctuations were monitored in a riverine system during and after Superstorm Sandy to better characterize inter-and intracommunity responses associated with the disturbance associated with a 100-year storm event. High-throughput sequencing of the 16S rRNA gene was used to assess microbial community structure within water samples from Muddy Creek Run, a second-order stream in Huntingdon, PA, at 12 different time points during the storm event (29 October to 3 Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 78 publications
(85 reference statements)
8
14
0
Order By: Relevance
“…The fluctuations of major bacterial groups and functional genes during two large storm events (shown by PCR‐DGGE, high throughput sequencing, and qPCR in the results) indicated that changes occurred during the storms, but the differences in bacterial communities were likely due to shifts in the relative abundance of species rather than variation in presence/absence. Similar observations were made at Muddy Creek Run, a second‐order stream in Huntingdon, PA, during Super Storm Sandy (Ulrich et al, ). To my knowledge, this study is the first of kind investigating bacterial community shifts in two sequential storm events with couple days apart.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The fluctuations of major bacterial groups and functional genes during two large storm events (shown by PCR‐DGGE, high throughput sequencing, and qPCR in the results) indicated that changes occurred during the storms, but the differences in bacterial communities were likely due to shifts in the relative abundance of species rather than variation in presence/absence. Similar observations were made at Muddy Creek Run, a second‐order stream in Huntingdon, PA, during Super Storm Sandy (Ulrich et al, ). To my knowledge, this study is the first of kind investigating bacterial community shifts in two sequential storm events with couple days apart.…”
Section: Discussionsupporting
confidence: 71%
“…These allochthonous particulate organic sources serve as a critical energy supply for biota living in the streams and therefore contribute to ecosystem metabolism and energy flow within aquatic food webs (Tank et al, ). In addition to the massive amount of particulate materials, the storm events also mobilize abundant particle‐associated microorganisms, and “mixing and seeding” of these “new” microorganisms could lead to significant changes on the composition and distribution of microorganisms in receiving streams (Staley et al, ; Ulrich et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The V4 region of the 16s rrn genes from bacterial DNAs were amplified by Illumina tag (itag) PCR using the 515F forward primer and the Illumina 806R reverse barcoded primer (16S Illumina Amplicon Protocol, http://www.earthmicrobiome.org). Individual barcoded samples were prepared and sequenced (Ulrich et al., ) by Wright Labs (Huntingdon, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Microbiota are the base of biogeochemical cycles [9] and act as a pollutant biodegradation, so it is essential to assess a microbial community structure's changing nature in aquatic systems. The structures of bacterial communities are affected by the hydrodynamics of storm events [10], physiochemical parameters, longitudinal distance, upstream inputs affects and fecal indicator bacteria concentrations. Further, bacterivory, substrate availability, variation in hydrological and nutrient conditions [11], land use changes, distance from the pristine headwaters, rainfall and pH [12] influence the structure of microbial communities in riverine environments.…”
Section: Introductionmentioning
confidence: 99%